Digital Transformation in Spain: The Role of Government in Digitalization Strategies - García Alonso, Roberto; Thoene, Ulf; Dávila Benavides, Diego Eduardo; Perez, Francisco Andrés (Law, State and Telecommunications Review, 2025)
[Purpose] This article examines the evolving role of the Spanish government in national digital transformation strategies, especially in the context of post-COVID-19 recovery and European digital policy frameworks. [Methodology/approach/design] The study employs a mixed-methods, single-case study design that integrates qualitative content analysis with semi-automated quantitative content analysis using the R programming language. It systematically analyzes national strategy documents to uncover the government’s role in digitalization policies over time. [Findings] The findings reveal a marked evolution in Spain’s digitalization strategies from early infrastructure-oriented initiatives toward a more comprehensive, cross-cutting approach led by central government institutions. Recent strategies, such as Digital Spain 2025 and 2026, reflect a growing emphasis on public investment and multi-level governance and a shift from hierarchical control to collaborative public-private frameworks. The government increasingly assumes a dual role as both regulator and innovation facilitator. [Practical implications] The study provides actionable insights for policymakers, highlighting how state-driven strategies can integrate public-private collaboration, prioritize digital inclusion, and align with broader EU objectives. It also illustrates the utility of content analysis tools in digital policy evaluation. [Originality/value] This research contributes to the literature on digital governance by offering a longitudinal analysis of Spain’s digital strategies and proposing a conceptual framework for understanding government roles in digital transformation. It reveals how the Spanish state combines hierarchical mechanisms with networked governance models to drive national digitalization.